Creation, Redemption and Theodicy in the Work of Christopher Southgate. Issue 2 (3rd April 2019) - Allen, Paul
ABSTRACT: This paper analyzes the work of Christopher Southgate with a view toward interpreting his insights into the integrity of creation, redemption and theodicy in light of Saint Augustine's theology. Drawing on various contributions that Southgate has made, this paper seeks to establish parallels, connections and some agreement between his work and the great African bishop without papering over the obvious disagreements over the Fall, Original Sin, the premises of salvation and biblical hermeneutics.